The Challenges of Apnea Tests in the Determination of Brain Death in Child Patient on Extracorporeal Membrane Oxygenation - Xu, Lingling; Liang, Yujian; Liao, Yuan; Rong, Jian; Xu, Guixing; Tang, Wen (Frontiers in Pediatrics, 2020)
Extracorporeal membrane oxygenation (ECMO) is a life-support modality used in patients with refractory cardiac and/or respiratory failure. ECMO is linked with high risk of neurological complications including brain death. Neurological monitoring during ECMO is important for identifying patients who are suspected of brain death and allows to discontinue ineffective medical treatments. Brain death (BD) is an irreversible cessation of functions of the entire brain,containing the brainstem. The apnea test (AT) is an essential part in the clinical determination of brain death. An apnea test is by neurologic criteria compulsory to confirm BD in china. Apnea test remains a problem for patients receiving ECMO. Currently, there are not any consensus guidelines for the safe performance of AT during ECMO. We report the case of a child on venous-arterial ECMO post-cardiac arrest in whom we performed an apnea test to determine death by neurologic criteria. Decreasing sweep gas flow rate 0.05L/min every 5 minute led to a PaCO2 increase of more than 20 mmHg of apnea. The results of the AT was positive. When he was determined brain dead, his parents decided to donate his organs. AT can be performed on potential donor children on ECMO by decreasing the sweep gas flow. It is a safe and effective method and is important for BD determination.